2015
DOI: 10.1002/stem.2050
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Have Innate Procoagulant Activity and Cause Microvascular Obstruction Following Intracoronary Delivery: Amelioration by Antithrombin Therapy

Abstract: Mesenchymal stem cells (MSCs) are currently under investigation as tools to preserve cardiac structure and function following acute myocardial infarction (AMI). However, concerns have emerged regarding safety of acute intracoronary (IC) MSC delivery. This study aimed to characterize innate prothrombotic activity of MSC and identify means of its mitigation toward safe and efficacious therapeutic IC MSC delivery post-AMI. Expression of the initiator of the coagulation cascade tissue factor (TF) on MSC was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 43 publications
7
102
0
Order By: Relevance
“…IA injection, which is already more risky because of the arterial puncture, also appears to entail a risk of development of microvascular occlusions called passive entrapment [27,46] . In addition, there have been reports that MSCs have a procoagulant activity [26,47] . A few years ago, a group from the Karolinska Institute reported that MSCs, particularly those that had been subjected to extended passaging and co-culture with activated lymphocytes, exhibited increased prothrombotic capacities; this effect was dose-dependent [47] .…”
Section: Msc Homing and Migration To Bone Marrow And Other Tissuesmentioning
confidence: 99%
See 3 more Smart Citations
“…IA injection, which is already more risky because of the arterial puncture, also appears to entail a risk of development of microvascular occlusions called passive entrapment [27,46] . In addition, there have been reports that MSCs have a procoagulant activity [26,47] . A few years ago, a group from the Karolinska Institute reported that MSCs, particularly those that had been subjected to extended passaging and co-culture with activated lymphocytes, exhibited increased prothrombotic capacities; this effect was dose-dependent [47] .…”
Section: Msc Homing and Migration To Bone Marrow And Other Tissuesmentioning
confidence: 99%
“…A few years ago, a group from the Karolinska Institute reported that MSCs, particularly those that had been subjected to extended passaging and co-culture with activated lymphocytes, exhibited increased prothrombotic capacities; this effect was dose-dependent [47] . Gleeson et al [26] reported that MSCs express functionally active tissue factor. When MSCs were injected in the coronary arteries of a porcine myocardial infarction model, it resulted in a decreased coronary flow reserve.…”
Section: Msc Homing and Migration To Bone Marrow And Other Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, bleeding is rare, even with very low platelet counts. A possible explanation is that bone marrow mesenchymal cells express tissue factor besides other procoagulants [11]. The guideline for therapy with blood components issued by the German Federal Medical Association (Bundesärztekammer) advises against platelet transfusions before BMBs, which reflects their general perception as low-risk procedures [12].…”
Section: Discussionmentioning
confidence: 99%